Accounting in Asia - S. Susela Devi; Hooper, Keith; Uddin, Shahzad; Tsamenyi, Mathew (Emerald, 2011)
This thematic volume covers issues such as Executive compensation and corporate governance with special reference to Bangladesh; leading companies in India; Fraudulent Financial Reporting; Non-financial performance measures and performance relationship in the Bangladeshi manufacturing firms; Fair value accounting usefulness and implementation Obstacles; Funding organisations: the conflict between the creative versus scientific approach of allocating funds in New Zealand; and more.
Keywords: Accounting -- Asia.; elektronické knihy; electronic books